Pengaruh Emotional Labour dan Reward terhadap Performa Kerja Karyawan Divisi Pemasaran PT MI - William Ben Gunawan; Angelica Herdyandra Setyani; Ghazlina Putri Perwitasari (Penerbit Goodwood, 2024)
Purpose: This study aims to deepen the understanding of the influence of emotional labor ability and rewards on employee performance, with a case study focusing on PT MI.Methodology: This study used a quantitative approach by collecting data using a questionnaire from 30 employees of the marketing division of PT MI. Statistical analyses were performed to examine employee characteristics, the validity and reliability of the questionnaire, the dimensions of variables, and the links between variables, mainly using multiple linear regression.Results: The results indicate that rewards significantly affect job performance, while emotional labor does not have a significant impact. Both independent variables simultaneously and significantly influence job performance. The coefficient of determination of 62.3% indicates that emotional labor and rewards can explain 62.3% of the variability in job performance, while the remaining variability is explained by other factors.Conclusions: It is concluded that emotional labor does not affect work performance. While rewards have a significant effect on work performance. Emotional labor and rewards together significantly affect work performance. Emotional labor and rewards can predict 62.3% of the value of work performance.Limitations: We face a limitation in collecting a higher number of respondents due to the limited number of employees in the marketing division of PT MI.Contribution: This study found that financial and non-financial rewards significantly enhance job performance through intrinsic and extrinsic motivation and psychological contracts between employees and the organization. In contrast, the lack of a significant impact of emotional labor may be due to individual differences in managing emotions, job characteristics, and other dominant factors, such as technical skills and intrinsic motivation. These findings underscore the importance of rewards in improving employee performance and the need for further research on the role of emotional labor in various contexts.